Comparative Analysis of the Effectiveness of Educational Methods on Public Knowledge of Infectious Disease Prevention in Urban and Rural Areas - Kalenggo, Ealani Putri (Generasi Sains Indonesia, 2024)
This take a look at ambitions to evaluate the effectiveness of instructional techniques in improving public know-how of infectious ailment prevention in urban and rural regions. A quantitative method become hired, with statistics gathered thru pre- and submit-intervention surveys. The effects indicate that both city and rural groups showed sizeable development in know-how rankings after the instructional intervention. However, the rural population verified a higher growth in information as compared to the city population. These findings advise that tailored educational strategies are vital for addressing the unique needs of different groups in improving public health know-how and, in the long run, enhancing health effects.